20‐2: Mixed‐Cation Perovskite Light‐Emitting Diodes with High Brightness and High Current Efficiency. Issue 1 (May 2017) - Xu, Bing; Zhang, Xiaoli; Wang, Weigao; Hao, Junjie; Deng, Jian; Sun, Xiaowei; Wang, Kai
Abstract : We demonstrate facile synthesis of perovskite nanocrystal based on (CH3 NH3 )1‐x Csx PbBr3 . The as‐obtained (CH3 NH3 )1‐x Csx PbBr3 nanocrystals are employed as emission layer in perovskite light emitting diodes, and the device shows high luminescence of 24000 cd/m 2, and high current efficiency of 4 cd/A.